Features of the psychophysiological development of younger schoolchildren with hearing impairments in the framework of the pedagogical model of physical education using swimming and tempering equipment - Aleksanyants, G.D.; Medvedeva, O.A.; Salnikova, E.A.; Malinovskiy, M.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the psychophysiological indicators in children aged 8–10 years with varying degrees of auditory deprivation. Methods and structure of the study. The observation was organised at a special (correctional) boarding school and the laboratory of the Department of Anatomy and Sports Medicine at the Kuban State University of Physical Culture, Sport and Tourism. The study included 29 pupils aged 8–10 years with varying degrees of auditory deprivation, engaged in the implementation of a pedagogical model of physical education using swimming and tempering activities, comprising 17 boys and 12 girls. The hardware-software computer complex "NS-PsychoTest" was used as the research instrument. The following indicators were assessed in the subjects: simple visual-motor reaction (SVMR), reaction to a moving object (RMO), "discrimination reaction" (DR), and "choice reaction" (CR). Results and conclusions. The simple visual-motor reaction indicators obtained during the study may be determined by anatomical features of the analyser, properties of nervous processes, the psychophysiological state of the body and the motor-coordination potential of the subject. As children mature, the sensorimotor reaction period decreases, which is associated with the maturation of central brain structures and the improvement of the functional state of the neuromuscular apparatus. In children aged 9–10 years, the degree of balance between excitation and inhibition processes in terms of strength is greater. This indicates a greater equilibrium of nervous processes and stability of nervous system functioning at this age. As children mature, the number of delayed and anticipatory reactions decreases significantly, which is due to the intensive development of central mechanisms.